2022
DOI: 10.1155/2022/6495044
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Acquired Pathogenic Escherichia coli from Clinical and Hospital Water Samples of Quetta Balochistan

Abstract: A study was conducted to determine the prevalence and drug resistance of Escherichia coli present in urinary tract infected patients and hospital drinking water. A total of eighty urine samples from clinically suspected patients and thirty tap water samples from hospital vicinity were collected and analyzed for the presence of E. coli. The isolates were preliminary identified based on morphological characteristics, biochemical test and further confirmed by polymerase chain reaction (PCR) using uidA primer. Iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
1
2
Order By: Relevance
“…The prevalence of E. coli found in our study is higher than that reported in Pakistan where 23.75% of E. coli were isolated from urine samples [100]. A study in Poland reported a higher E. coli isolation rate of 78% (identified using 16S rRNA sequencing) and 82% (identified using MALDI Biotype) from river water and wastewater [100]. However, our isolation rate of E. coli from water samples was lower compared to that reported in Pakistan where the researchers found an isolation rate of 26.7% [100].…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…The prevalence of E. coli found in our study is higher than that reported in Pakistan where 23.75% of E. coli were isolated from urine samples [100]. A study in Poland reported a higher E. coli isolation rate of 78% (identified using 16S rRNA sequencing) and 82% (identified using MALDI Biotype) from river water and wastewater [100]. However, our isolation rate of E. coli from water samples was lower compared to that reported in Pakistan where the researchers found an isolation rate of 26.7% [100].…”
Section: Discussioncontrasting
confidence: 87%
“…Our low prevalence of E. coli isolated from the environment compared to the hospital setting could be due to the challenges in isolation methods of E. coli from environmental samples [ 99 ]. The prevalence of E. coli found in our study is higher than that reported in Pakistan where 23.75% of E. coli were isolated from urine samples [ 100 ]. A study in Poland reported a higher E. coli isolation rate of 78% (identified using 16S rRNA sequencing) and 82% (identified using MALDI Biotype) from river water and wastewater [ 100 ].…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation